Mejoramiento de la calidad de vida de la población escolar, del segundo año de educación básica paralelos a- b de la escuela “Marieta de Veintimilla” del barrio Motupe, parroquia El Valle, cantón y provincia de Loja, mediante la atención básica bucodental considerando su perfil epidemiologico. Periodo marzo – septiembre 2010 - Salinas Salinas, Tania Soledad (2010)
The investigation there carried out in the School "Marieta de Veintimilla" Of The Neighborhood Motupe, in Loja's Province, north sector of the city, in the period March - September, 2010, with the participation of the investigator, director of thesis and the school teachers, family, parents and students. The intention was students knew the pathologies more frequents and control it same to improve the quality of life of the children in Second Year of Education parallel "A-B" of the school in mention, across a diagnosis and basic rehabilitation, during the indicated period, for which was necessary the production of the raising of the epidemiological oral profile of the population in study, the education on oral health to parents and schoolmates and the treatment of the principal oral pathologies according to the epidemiological profile. It was a study of character , Descriptive and of Intervention constituted by a population of 727 children, belonging to different schools of the area of abundance to Motupe's University Hospital of the Area Of Health N ° 3; the sample to investigating is of forty boys and girls of the Second Year of Basic Education, of which 30 belong to the parallel A, and 11 of parallel B, to whom they the diagnosis was realized, seating the information in the clinical history on the Career of Odontolgy of Loja's National University and in the Motupe's University Hospital and the following results were obtained: 19 children and 14 girls attended, in age of 6 and 7 years. As for the index ceod, in the children it is in 8,94, and in the girls with 7,14, both in HIGH risk. While the index CPOD is in risk I GO DOWN since in the masculine sex we have 0,47 and in the feminine sex 0,21. As for the pathologies of the hard fabrics and softs, the caries affects the whole school population studied in 100 %. In six-year-old children the percentage of badly position dentaria is 57,14 %, pathology pulpar and pigmentations 50%, 35,71% tongue saburral and 28, 57% inflamed gum; in the age of seven years old 80 % of pathology pulpar, badly position dentaria 40%, tongue saburral 80% and inflamed gum 20%,; in the girls of six - years-old the percentage more higest is in: pigmentations 50 %, badly position dentaria and pathology pulpar 33,33 %; whereas in the age of seven years we find 50 % of pigmentations, pathology pulpar and badly occlusion, and inflammation of the gums in 20 %. Concluding that the pathologies more prevalent are in the hard and soft fabrics; whose factors predisponentes to these diseases are the bacterial plate, and white matter that one finds in 100 % in the same age and gender. Population it was controlled by means of treatments as: application of sellantes, operative dental simple and compound, therapy pulpar (pulpotomía and pulpectomía), minor surgery, prevention, application of fluorine and presidents' placement of space. Finally one educated and instructed in oral health the children and family parents of the school by means of chats and demonstrations as well as the delivery of elements for oral hygiene and informative outlets. Key words: CPOD, ceod, caries, pathology pulpar.